2019
DOI: 10.1108/sef-12-2017-0350
|View full text |Cite
|
Sign up to set email alerts
|

Does personality drive price bubbles?

Abstract: Purpose The purpose of this study is to analyze whether differences in market-wide levels of investor personality influence experimental asset market outcomes in terms of limit orders, price levels and price bubbles. Design/methodology/approach Investor personality is determined by a questionnaire. These data are combined with data from 17 experimental asset markets. Two approaches are used to estimate market-wide levels of investor personality. First, the market-wide average of each personality trait is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The findings in this paper show that the psychopathy trait plays an important role in financial decision-making. Our results add to the growing literature that personality traits (in our case, abnormal traits) drive many investment choices (Chitra and Sreedevi, 2011; Conlin et al , 2015), stock market performance (Durand et al , 2008), the disposition effect (Durand et al , 2013a), overconfidence (Durand et al , 2013b), risk aversion (Filbeck et al , 2005), loss aversion (Durand et al , 2019), trading behavior (Durand et al , 2008; Durand et al , 2013a; Tauni et al , 2017; Oehler et al , 2018; Oehler et al , 2019), risk tolerance (Wong and Carducci, 2016) and financial delinquency (Parise and Peijnenburg, 2017). In focusing only on psychopathic traits in the current analysis, we leave the question of how other psychological models might relate to the variables modeled in this paper for future research.…”
Section: Introductionsupporting
confidence: 70%
“…The findings in this paper show that the psychopathy trait plays an important role in financial decision-making. Our results add to the growing literature that personality traits (in our case, abnormal traits) drive many investment choices (Chitra and Sreedevi, 2011; Conlin et al , 2015), stock market performance (Durand et al , 2008), the disposition effect (Durand et al , 2013a), overconfidence (Durand et al , 2013b), risk aversion (Filbeck et al , 2005), loss aversion (Durand et al , 2019), trading behavior (Durand et al , 2008; Durand et al , 2013a; Tauni et al , 2017; Oehler et al , 2018; Oehler et al , 2019), risk tolerance (Wong and Carducci, 2016) and financial delinquency (Parise and Peijnenburg, 2017). In focusing only on psychopathic traits in the current analysis, we leave the question of how other psychological models might relate to the variables modeled in this paper for future research.…”
Section: Introductionsupporting
confidence: 70%
“…Another reason is that, contrary to the other personality traits, extraversion and neuroticism are strongly connected with emotional states (Costa & McCrae, 1980; Larsen & Ketelaar, 1989), locus of control (Kovaleva, Beierlein, Kemper, & Rammstedt, 2012; Morris & Carden, 1981; Oehler, Wendt, Wedlich, & Horn, 2017), and cognition, that is, information processing in the form of focusing on positive and negative information (Noguchi, Gohm, & Dalsky, 2006) that largely influences individuals’ risk-taking behavior (Forgas, 1995; Grable & Roszkowski, 2008; Isen & Patrick, 1982; Karlsson, Loewenstein, & Seppi, 2009; McInish, 1980; Slovic, 1972). Moreover, it is shown that investors’ degree of extraversion and neuroticism both at the individual and the market-wide level has an impact on individual trading behavior and market outcomes in terms of price bubbles and levels (Oehler, Wedlich, Wendt, & Horn, 2016). This leads us to assume that extraversion and neuroticism are both important factors that influence the determinants of risk-taking.…”
mentioning
confidence: 99%
“…Some of the most popular include overconfidence, overreaction, underreaction, wishful thinking, procrastination, anchoring and myopia (Ramiah et al, 2015;Frydman and Camerer, 2016;Liu and Tan, 2021;Kleine et al, 2022). In approaching investors' behavior, it is also important to account for the different personalities of investors, which surely determine the direction and intensity of the observed biases (Kleine et al, 2016(Kleine et al, , 2020(Kleine et al, , 2021De Bortoli et al, 2019;Gambetti and Giusberti, 2019;Oehler et al, 2021).…”
Section: Favorite Subfield: Behavioral Financementioning
confidence: 99%